The Interplay between PR Messaging and Loyalty in Young Adult Markets: A Study from Medan City - Widjaya, Arifa Dani Anggit; Ramonita, Latifa (Journal of Communication and Public Relations, 2025)
As public awareness of environmental and social issues grows, consumers increasingly gravitate toward brands that demonstrate a commitment to sustainability and social responsibility. This shift has prompted businesses to launch campaigns that address these concerns, effectively aligning their values with those of their target audiences. Within the beauty industry, The Body Shop’s "Be Seen Be Heard" campaign serves as a prime example, promoting environmental and social values while engaging consumers. This study examines the relationship between such public relations messaging and consumer loyalty among young adults in Medan City. A quantitative research approach was employed, with data collected from 100 respondents through structured questionnaires. Correlation analysis revealed a strong and significant positive relationship between the PR campaign and consumer loyalty, with a coefficient of 0.823. This result underscores the campaign's effectiveness in fostering loyalty within the young urban demographic by aligning brand messaging with issues of social and environmental relevance. The findings emphasize the strategic role of public relations in shaping consumer perceptions and behaviors, particularly among socially conscious young adults. They also highlight the importance of authentic, values-driven campaigns in cultivating long-term brand loyalty. This study contributes to the growing body of knowledge on the interplay between PR messaging and consumer loyalty, offering practical insights for businesses aiming to strengthen their market presence in the era of sustainability.